2019
DOI: 10.3389/fphar.2019.00260
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Combined With Gefitinib Blocks Autophagy Flux and Induces Apoptotic Cell Death Through Inhibition of HIF-1α, c-Myc, p-EGFR, and Glucose Metabolism in EGFR L858R+T790M-Mutated H1975 Cells

Abstract: Cancer cells are characterized by abnormally increased glucose uptake and active bio-energy and biosynthesis to support the proliferation, metastasis, and drug resistant survival. We examined the therapeutic value of the combination of apigenin (a natural small-molecule inhibitor of Glut1 belonging to the flavonoid family) and gefitinib on epidermal growth factor receptor (EGFR)-resistant mutant non-small cell lung cancer, to notably damage glucose utilization and thus suppress cell growth and malignant behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
(40 reference statements)
0
27
0
Order By: Relevance
“…For example, combination of apigenin and gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, to treat EGFR-resistant mutant non-small cell lung cancers impairs energy utilization and suppresses cell growth and malignant behavior. They inhibit the activity of several oncogenic drivers such as MYC, HIF1α, and EGFR, reduce the protein expression of Gluts and MCT1, and inactivate the 5 adenosine monophosphate-activated protein kinase (AMPK) signaling (Chen Z. et al, 2019). Together, targeting these downstream signaling pathways controlled by MYC-HIF crosstalk (Figure 2E) or directly co-targeting MYC and HIFs could emerge as effective therapeutics in advanced human cancers such as advanced ccRCCs.…”
Section: Targeting Myc-hif Crosstalk For Cancer Therapymentioning
confidence: 99%
“…For example, combination of apigenin and gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, to treat EGFR-resistant mutant non-small cell lung cancers impairs energy utilization and suppresses cell growth and malignant behavior. They inhibit the activity of several oncogenic drivers such as MYC, HIF1α, and EGFR, reduce the protein expression of Gluts and MCT1, and inactivate the 5 adenosine monophosphate-activated protein kinase (AMPK) signaling (Chen Z. et al, 2019). Together, targeting these downstream signaling pathways controlled by MYC-HIF crosstalk (Figure 2E) or directly co-targeting MYC and HIFs could emerge as effective therapeutics in advanced human cancers such as advanced ccRCCs.…”
Section: Targeting Myc-hif Crosstalk For Cancer Therapymentioning
confidence: 99%
“…In addition to the induction of apoptotic/necrotic cell death, our results also demonstrated that autophagic cell death and Sphase arrest ( Supplementary Figures 1 and 2) contributed to the cytocidal effects of the combined regimen of 10 mM As III +6.4 mM Tetra in MDA-MB-231 cells. Although autophagy has been linked to apoptotic/necrotic cell death in many cases (Nikoletopoulou et al, 2013;Yoshida, 2017;Chen et al, 2019), our experimental results demonstrated that the addition of either 3-MA or wortmannin, two autophagy inhibitors, successfully corrected the combined regimen-triggered S-phase arrest, however, had little effect on the apoptosis/necrosis induction (Figures 4 and 5). Autophagy has been demonstrated to act either as a cytoprotective process or a pro-death factor in different cellular contexts (White and DiPaola, 2009; After treatment with 10 mM As III +6.4 mM Tetra in the presence or absence of 3-MA (0.25, 1.0 mM) or wortmannin (0.25, 1.0 mM) for 48 h, cell cycle profiling was performed by FACSCanto flow cytometer.…”
Section: Discussionmentioning
confidence: 74%
“…Herein, both the induction of autophagy and S-phase arrest were first confirmed in MDA-MB-231 cells following the exposure to the combined regimen of 10 mM As III +6.4 mM Tetra for 48 h ( Supplementary Figures 1 and 2). Previous studies have demonstrated a close association between autophagy and apoptosis as well as cell cycle arrest induction in different types of cancer cells including MDA-MB-231 (Cheng et al, 2015;Gao et al, 2015;Lee et al, 2016;Lin et al, 2016;Chen et al, 2019). In order to clarify whether there was a link between autophagy and apoptosis/necrosis as well as S-phase arrest, two autophagy inhibitors, 3-MA and wortmannin, were used in the current study.…”
Section: Autophagy Contributed To the Cytotoxicity Of As III Combinedmentioning
confidence: 99%
“…Overall, we believe there is enough support to warrant clinical trials for the use of apigenin, as there is a growing body of researching showing its antitumor effects from multiple stand points from blocking mutagenic induced cancers [e.g., methyl-nitrosourea, methyl-n-nitro-N-nitrosoguanidine, benzo(a)pyrene or 2-aminoanthracene] (88) to inhibition of ornithine decarboxylase (89) and its overall antioxidant, anti-inflammatory effects (90,91). Data on the clinical efficacy of substances like apigenin for human use to reduce CLL2 will also need to be confirmed, as well as establishing its bioavailability, absorption, therapeutic concentration and application (prevention, treatment or for chemotherapy drug augmentation) (55,(91)(92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%